Long-term, West Nile virus-induced neurological changes: A comparison of patients and rodent models - Fulton, Corey D.M.; Beasley, David W.C.; Bente, Dennis A.; Dineley, Kelly T. (Brain, behavior, & immunity. Health, 2020)
West Nile virus (WNV) is a mosquito-borne virus that can cause severe neurological disease in those infected. Those surviving infection often present with long-lasting neurological changes that can severely impede their lives. The most common reported symptoms are depression, memory loss, and motor dysfunction. These sequelae can persist for the rest of the patients’ lives. The pathogenesis behind these changes is still being determined. Here, we summarize current findings in human cases and rodent models, and discuss how these findings indicate that WNV induces a state in the brain similar neurodegenerative diseases. Rodent models have shown that infection leads to persistent virus and inflammation. Initial infection in the hippocampus leads to neuronal dysfunction, synapse elimination, and astrocytosis, all of which contribute to memory loss, mimicking findings in neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). WNV infection acts on pathways, such as ubiquitin-signaled protein degradation, and induces the production of molecules, including IL-1β, IFN-γ, and α-synuclein, that are associated with neurodegenerative diseases. These findings indicate that WNV induces neurological damage through similar mechanisms as neurodegenerative diseases, and that pursuing research into the similarities will help advance our understanding of the pathogenesis of WNV-induced neurological sequelae. •In patients with and without diagnosed WNND, there are long-lasting neurological sequelae that can mimic neurodegenerative diseases.•Some rodent models of WNV reproduce some of these changes with mechanisms similar to neurodegenerative diseases.•There is significant overlap between WNV and ND pathogenesis and this has been understudied.•Further research needs to be done to determine accuracy of animal models compared to human patients.